2016
DOI: 10.1155/2016/5876798
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Multifocal Leukoencephalopathy in a Multiple Sclerosis Patient Diagnosed after Switching from Natalizumab to Fingolimod

Abstract: Background. Natalizumab- (NTZ-) associated progressive multifocal leukoencephalopathy (PML) is a severe and often disabling infectious central nervous system disease that can become evident in multiple sclerosis (MS) patients after NTZ discontinuation. Recently, novel diagnostic biomarkers for the assessment of PML risk in NTZ treated MS patients such as the anti-JC virus antibody index have been reported, and the clinical relevance of milky-way lesions detectable by MRI has been discussed. Case Presentation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…To our knowledge, four cases of PML‐IRIS during FTY treatment have been reported so far, and all were linked to prior NTZ therapy 82, 83, 84, 85. Killestein et al reported a 52‐year‐old RRMS male patient switched to FTY from NTZ as a result of a positive JCV antibody test 82.…”
Section: Fingolimod and Progressive Multifocal Leukoencephalopathy‐rementioning
confidence: 99%
“…To our knowledge, four cases of PML‐IRIS during FTY treatment have been reported so far, and all were linked to prior NTZ therapy 82, 83, 84, 85. Killestein et al reported a 52‐year‐old RRMS male patient switched to FTY from NTZ as a result of a positive JCV antibody test 82.…”
Section: Fingolimod and Progressive Multifocal Leukoencephalopathy‐rementioning
confidence: 99%
“…- 144 The latest evidence suggests that no washout period is recommended 113 . However, since both drugs carry a risk of PML, it would be important to perform an “exit MRI” and CSF for JCV PCR before initiating fingolimod as there have been many cases of “carry-over” PML from natalizumab-treated patients initiated on fingolimod 145 146 …”
Section: Course To Follow When Considering Treatment Modificationmentioning
confidence: 99%
“…Fingolimod's main effect in MS is mediated by retention of lymphocytes in lymphnodes (Mehling et al, 2011;Matloubian et al, 2004;Mandala et al, 2002). Although 19 cases of PML have been reported to date on official quarterly updates (Calic et al, 2015;Killestein et al, 2014;Peaureaux et al, 2015;Sinnecker et al, 2016), the risk of developing PML under fingolimod is regarded as low (0.069/1000) (Berger et al, 2018;Berger, 2017). An analysis of data from the MSBase Registry (Jokubaitis et al, 2014) indicated that rebound disease activity is not to be expected after switching from natalizumab to fingolimod.…”
Section: Introductionmentioning
confidence: 99%